The effects of mindfulness practices on well-being - Calin, Mariana Floricica; Ginara, Diana Maria (Technium Social Sciences Journal, 2023)
There is growing interest in psychological research into mindfulness practices and their association with aspects of psychological functioning and well-being. Therefore, we have carried out this research with the main purpose of reducing prejudices and limiting beliefs about mindfulness practices and to present the benefits of mindfulness practices on well-being¸ with its many benefits. Aiming to confirm and extend previous knowledge on this topic, we studied the relationships between well-being and the quality of mindfulness practices in a sample (N: 59), adopting a multidimensional conceptualization of mindfulness. To begin with, we performed a simple linear regression to determine whether the mindfulness variable predicts the individual’s psychological well-being. The results, analyzed from a statistical point of view, show that 52.9% of the well-being of the respondents is influenced by the practice of mindfulness. Thus, the practice of mindfulness techniques influences and is an important predictor of psychological well-being. Then, we correlated the construct of mindfulness with that of well-being and all its facets: autonomy, mastery of the environment, personal growth, positive relationships with others, purpose in life and self-acceptance. For this, we used two questionnaires: the Five Facets Mindfulness Questionnaire (FFMQ) and the questionnaire that measures the well-being construct, the Ryff Scale. The results showed direct, strong correlations, both between mindfulness and the scores obtained for the well-being construct, as well as for the relationship between mindfulness practice and the subscales of the Riff instrument: autonomy, mastery of the environment, personal growth, positive relationships with others and self-acceptance. The correlation between mindfulness and purpose in life is direct and average. This study supports the relationship between mindfulness and psychological well-being, with evidence that the practice of mindfulness can enhance an individual’s well-being through various means